Handbook of dredging engineering - Herbich, John B. (McGraw-Hill, 2000)
From selecting the right equipment, to evaluating environmental impact, to bidding on a project, Handbook of Dredging Engineering, Second Edition, is the last word on modern hydraulic dredging. Edited by John B. Herbich, with contributions by well-know experts in the field, the Handbook examines basic fluid mechanics; dredge pumps; dredging equipment; sediment; pipeline transport of solids; dredging methods; disposal and placement of dredged material; numerical models for predicting the fate of dredged material placed in open water; environmental effects of dredging activities; instrumentation and automation; and project planning. This vital new edition covers major advances made over the last seven years. Three chapters are new to this edition: numerical models for predicting the fate of dredged material...subaqueous capping of contaminated sediment...and removal of contaminated sediments by dredging, with illustrative case studies.